Correlation between mass and volume of collected blood with positivity of blood cultures. (December 2015) - Neves, Lariessa; Marra, Alexandre; Camargo, Thiago; Santos, Maura; Zulin, Flávia; Silva, Patrícia; Moura, Natália; Silva Victor, Elivane; Pasternak, Jacyr; Santos, Oscar; Edmond, Michael; Martino, Marines
Abstract Background The collection of blood cultures is an extremely important method in the management of patients with suspected infection. Microbiology laboratories should monitor blood culture collection. Methods Over an 8-month period we developed a prospective, observational study in an adult Intensive Care Unit (ICU). We correlated the mass contained in the blood vials with blood culture positivity and we also verified the relationship between the mass of blood and blood volume collected for the diagnosis of bloodstream infection (BSI), as well as we explored factors predicting positive blood cultures. Results We evaluated 345 patients with sepsis, severe sepsis or septic shock for whom blood culture bottles were collected for the diagnosis of BSI. Of the 55 patients with BSI, 40.0 % had peripheral blood culture collection only. BSIs were classified as nosocomial in 34.5 %. In the multivariate model, the blood culture mass (in grams) remained a significant predictor of positivity, with an odds ratio 1.01 (i.e., for each additional 1 mL of blood collected there was a 1 % increase in positivity; 95 % CI 1.01–1.02, p = 0.001; Nagelkerke R Square [R2 ] = 0.192). For blood volume collected, the adjusted odds ratio was estimated at 1.02 (95 % CI: 1.01–1.03, p < 0.001; R2  = 0.199). For each set of collected blood cultures beyond one set, the adjusted odds ratio was estimated to be 1.27 (95 % CI: 1.14–1.41, p < 0.001; R2  = 0.221). Conclusions Our study was a quality improvement project that showed that microbiology laboratories can use the weight of blood culture bottles to determine if appropriate volume has been collected to improve the diagnosis of BSI.